Entrepreneurial Law in the Field of Health Services in Electronic Medical Records - Sultan, Muh Arsul Haq; Makanung, Rudy; Ansar, Muhammad Aksa; Leleallo, Wisye Riska; Wiyanti, Ayu Sri; Alrahmi, Nurul; Wahyuningsih, Sri (Gema Wiralodra, 2025)
Entrepreneurship in the field of Electronic Medical Records (EMR)-based healthcare services presents both opportunities and challenges related to legal compliance, patient data protection, and professional ethics. This study aims to analyze the relevant legal aspects of EMR implementation and their implications for business model development and healthcare service innovation.The method used is a systematic literature study with a qualitative-descriptive approach. Literature was obtained from academic databases and public repositories using the keywords "Electronic Medical Records", "health entrepreneurship", "health law", "privacy by design", and "telemedicine regulation" for the period 2020–2025. The analysis was conducted through thematic/content analysis with a focus on four main themes: the regulatory framework and legality of EMR, the implications of EMR for entrepreneurship and technology governance, legal risks and protection of healthcare workers, and  implementation barriers related to infrastructure, human resources, and interoperability. The study results indicate that the implementation of EMR plays a crucial role as a legal instrument, a means of digitizing services, and a basis for developing a regulatory-compliant entrepreneurial model. Implementation challenges include limited infrastructure, disparities in healthcare workforce competency, and varying levels of preparedness in healthcare facilities. Integrating legal principles, such as privacy by design and role-based access control, is key to minimizing legal risks while strengthening patient and stakeholder trust.In conclusion, strengthening the legal aspects of RME-based healthcare entrepreneurship is a prerequisite for ensuring a balance between innovation, legal protection, and business sustainability, while simultaneously improving the quality of healthcare services nationally.